DABCO- and DBU-promoted one-pot reaction of N-sulfonyl ketimines with Morita–Baylis–Hillman carbonates: a sequential approach to (2-hydroxyaryl)nicotinate derivatives - Guin, Soumitra; Gupta, Raman; Majee, Debashis; Samanta, Sampak (Beilstein Journal of Organic Chemistry, 2018)
An intriguing DABCO-catalyzed and DBU-promoted one-pot synthesis of an important class of (2-hydroxyaryl)pyridine derivatives bearing a carboxylate or a nitrile group suitably placed at C3 position of the aza-ring has been achieved in acceptable chemical yields with a broad functional group tolerance. This sequential C–C/C–N bond making process proceeds through a regioselective allylic alkylation/aza-Michael reaction between MBH carbonates derived from an acrylate/acrylonitrile and N-sulfonyl ketimines as C,N-binucleophiles catalyzed by DABCO, followed by elimination of SO2 under the influence of base and subsequent aromatization in an open atmosphere.
Keywords: MBH carbonates; metal-free; N-sulfonyl ketimines; one-pot sequential; pyridines

(untitled) - Heller, B.; Hapke, M. (Chem. Soc. Rev., 2007)

(untitled) - Allais, C.; Grassot, J.-M.; Rodriguez, J.; Constantieux, T. (Chem. Rev., 2014)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2005)

(untitled) - Guan, A.-Y.; Liu, C.-L.; Sun, X.-F.; Xie, Y.; Wang, M.-A. (Bioorg. Med. Chem., 2016)

(untitled) - Baumann, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2013)

Chemistry of Heterocyclic Compounds: Pyridine Metal Complexes - Tomasik, P.; Ratajewicz, Z.; Newkome, G. R.; Strekowski, L. (σ-Pyridine Coordination Compounds with Transition Metals, 1985)
Part 6.

(untitled) - Sumby, C. J. (Coord. Chem. Rev., 2011)

Functional Organic Materials - Müller, T. J. J.; Bunz, U. H. F. (Wiley-VCH, 2007)

(untitled) - Sasabe, H.; Kido, J. (Chem. Mater., 2011)

(untitled) - Hantzsch, A. (Ber. Dtsch. Chem. Ges., 1881)

(untitled) - Chichibabin, A. E. (J. Russ. Phys.-Chem. Soc., 1906)

(untitled) - Li, Z.; Huang, X.; Chen, F.; Zhang, C.; Wang, X.; Jiao, N. (Org. Lett., 2015)

(untitled) - Zhang, Q.-R.; Huang, J.-R.; Zhang, W.; Dong, L. (Org. Lett., 2014)

(untitled) - Martin, R. M.; Bergman, R. G.; Ellman, J. A. (J. Org. Chem., 2012)

(untitled) - Chen, S.; Bergman, R. G.; Ellman, J. A. (Org. Lett., 2015)

(untitled) - Neely, J. M.; Rovis, T. (J. Am. Chem. Soc., 2014)

(untitled) - Too, P. C.; Noji, T.; Lim, Y. J.; Li, X.; Chiba, S. (Synlett, 2011)

(untitled) - Wu, J.; Xu, W.; Yu, Z.-X.; Wang, J. (J. Am. Chem. Soc., 2015)

(untitled) - Goswami, A.; Ohtaki, K.; Kase, K.; Ito, T.; Okamoto, S. (Adv. Synth. Catal., 2008)

(untitled) - Hapke, M.; Kral, K.; Fischer, C.; Spannenberg, A.; Gutnov, A.; Redkin, D.; Heller, B. (J. Org. Chem., 2010)

(untitled) - Tanaka, K.; Suzuki, N.; Nishida, G. (Eur. J. Org. Chem., 2006)

(untitled) - Komine, Y.; Tanaka, K. (Org. Lett., 2010)

(untitled) - Onodera, G.; Shimizu, Y.; Kimura, J.-n.; Kobayashi, J.; Ebihara, Y.; Kondo, K.; Sakata, K.; Takeuchi, R. (J. Am. Chem. Soc., 2012)

(untitled) - Kumar, P.; Prescher, S.; Louie, J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yamamoto, Y.; Kinpara, K.; Ogawa, R.; Nishiyama, H.; Itoh, K. (Chem. – Eur. J., 2006)

(untitled) - Wang, C.; Li, X.; Wu, F.; Wan, B. (Angew. Chem., Int. Ed., 2011)

(untitled) - Tan, W. W.; Ong, Y. J.; Yoshikai, N. (Angew. Chem., Int. Ed., 2017)

(untitled) - Jiang, H.; Yang, J.; Tang, X.; Li, J.; Wu, W. (J. Org. Chem., 2015)

(untitled) - Wu, Q.; Zhang, Y.; Cui, S. (Org. Lett., 2014)

(untitled) - Senaiar, R. S.; Young, D. D.; Deiters, A. (Chem. Commun., 2006)

(untitled) - Sasada, T.; Sakai, N.; Konakahara, T. (J. Org. Chem., 2008)

(untitled) - He, Z.; Dobrovolsky, D.; Trinchera, P.; Yudin, A. K. (Org. Lett., 2013)

(untitled) - Allais, C.; Constantieux, T.; Rodriguez, J. (Chem. – Eur. J., 2009)

(untitled) - Mai, D. N.; Baxter, R. D. (Org. Lett., 2016)

(untitled) - Stephens, D.; Larionov, O. V. (Tetrahedron, 2015)

(untitled) - Engle, K. M.; Yu, J.-Q. (J. Org. Chem., 2013)

(untitled) - Liéby-Muller, F.; Allais, C.; Constantieux, T.; Rodriguez, J. (Chem. Commun., 2008)

(untitled) - Allais, C.; Liéby-Muller, F.; Rodriguez, J.; Constantieux, T. (Eur. J. Org. Chem., 2013)

(untitled) - Bohlmann, F.; Rahtz, D. (Chem. Ber., 1957)

(untitled) - Bagley, M. C.; Glover, C.; Merritt, E. A. (Synlett, 2007)

(untitled) - Bagley, M. C.; Chapaneri, K.; Dale, J. W.; Xiong, X.; Bower, J. (J. Org. Chem., 2005)

(untitled) - Gade, N. R.; Devendram, V.; Pal, M.; Iqbal, J. (Chem. Commun., 2013)

(untitled) - Song, Z.; Huang, X.; Yi, W.; Zhang, W. (Org. Lett., 2016)

(untitled) - Wan, J.-P.; Jing, Y.; Hu, C.; Sheng, S. (J. Org. Chem., 2016)

(untitled) - Kumar, S.; Sawant, A. A.; Chikhale, R. P.; Karanjai, K.; Thomas, A. (J. Org. Chem., 2016)

(untitled) - Reddy, C. R.; Panda, S. A.; Reddy, M. D. (Org. Lett., 2015)

(untitled) - Prechter, A.; Henrion, G.; Faudot dit Bel, P.; Gagosz, F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Tejedor, D.; Méndez-Abt, G.; García-Tellado, F. (Eur. J. Org. Chem., 2010)

(untitled) - Tejedor, D.; Méndez-Abt, G.; García-Tellado, F. (Chem. – Eur. J., 2010)

(untitled) - Jiang, Y.; Park, C.-M.; Loh, T.-P. (Org. Lett., 2014)

(untitled) - Jiang, Y.; Park, C.-M. (Chem. Sci., 2014)

(untitled) - Robert, N.; Bonneau, A.-L.; Hoarau, C.; Marsais, F. (Org. Lett., 2006)

(untitled) - Yu, J.; Kim, K. H.; Lee, H. J.; Kim, J. N. (Bull. Korean Chem. Soc., 2013)

(untitled) - Ling, F.; Xiao, L.; Fang, L.; Lv, Y.; Zhong, W. (Adv. Synth. Catal., 2018)

(untitled) - Hirai, S.; Horikawa, Y.; Asahara, H.; Nishiwaki, N. (Chem. Commun., 2017)

(untitled) - Longstreet, A. R.; Rivalti, D.; McQuade, D. T. (J. Org. Chem., 2015)

(untitled) - Longstreet, A. R.; Opalka, S. M.; Campbell, B. S.; Gupton, B. F.; McQuade, D. T. (Beilstein J. Org. Chem., 2013)

(untitled) - Shintani, T.; Kadono, H.; Kikuchi, T.; Schubert, T.; Shogase, Y.; Shimazaki, M. (Tetrahedron Lett., 2003)

(untitled) - Qi, X.; Xiang, H.; He, Q.; Yang, C. (Org. Lett., 2014)

(untitled) - Das, P.; Saha, D.; Guin, J. (ACS Catal., 2016)

(untitled) - Dong, J.; Liu, P.; Sun, P. (J. Org. Chem., 2015)

(untitled) - Yan, Y.; Feng, P.; Zheng, Q.-Z.; Liang, Y.-F.; Lu, J.-F.; Cui, Y.; Jiao, N. (Angew. Chem., Int. Ed., 2013)

(untitled) - Yamaguchi, T.; Yamaguchi, E.; Tada, N.; Itoh, A. (Adv. Synth. Catal., 2015)

(untitled) - Wu, Y.; Zhou, B. (Org. Lett., 2017)

(untitled) - Kim, K.; Hyun, J.; Kim, J.; Kim, H. (Asian J. Org. Chem., 2017)

(untitled) - Shome, S.; Singh, S. P. (Tetrahedron Lett., 2017)

(untitled) - Majee, D.; Biswas, S.; Mobin, S. M.; Samanta, S. (J. Org. Chem., 2016)

(untitled) - Majee, D.; Biswas, S.; Mobin, S. M.; Samanta, S. (Org. Biomol. Chem., 2017)

(untitled) - Majee, D.; Guin, S.; Biswas, S.; Samanta, S. (ChemistrySelect, 2017)

(untitled) - Biswas, S.; Majee, D.; Guin, S.; Samanta, S. (J. Org. Chem., 2017)

(untitled) - Guin, S.; Majee, D.; Biswas, S.; Samanta, S. (Asian J. Org. Chem., 2018)

Organic Synthesis Highlights V - Langer, P. (Wiley-VCH, 2003)

(untitled) - Langer, P. (Angew. Chem., Int. Ed., 2000)

(untitled) - Chen, X.-Y.; Gao, Z.-H.; Song, C.-Y.; Zhang, C.-L.; Wang, Z.-X.; Ye, S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Arupula, S. K.; Guin, S.; Yadav, A.; Mobin, S. M.; Samanta, S. (J. Org. Chem., 2018)